Perceived Peer Relationships in Adolescence and Loneliness in Emerging Adulthood and Workplace Contexts - Chiao, Chi; Lin, Kuan-Chen; Chyu, Laura (Frontiers in Psychology, 2022)
Background: A common life-course hypothesis is that negative early-life experiences contribute to poor health in later-life. However, little is known about perceived peer relationships during adolescence and the feeling of loneliness in emerging adulthood. The purpose of this study thus aims to explore the perception of adolescent peer relationships in a school context and its association with adult’s loneliness and in workplace contexts. Methods: A cohort sample of 2,520 adolescents from the Taiwan Youth Project (N=2,520) was analyzed, consisting of eleven waves of data collected from 2000 to 2017. The major measures included the Loneliness Scale (6-item de Jong Gierveld short scale) and perceived peer relationships (classroom cohesion and perceived popularity among classmates) in middle school. Multivariate multinomial logistic regressions were used to estimate the associations of perceived peer relationships during adolescence and workplace characteristics with adult loneliness. Results: Positive perceived peer relationships in adolescence were significantly related to decreased risk of serious social loneliness (Relative risk ratios [RRR] 0.70, 95% CI: 0.58-0.85) and severe social/emotional loneliness (RRR = 0.76, 95% CI: 0.63-0.91) in adulthood. Workplace satisfaction was a protective factor of severe social/emotional loneliness in employed adults. Conclusions: Adolescents who perceived positive peer relationships in middle school are less likely to report loneliness in the social and emotional domains during adulthood. Satisfaction in the workplace characteristics is also associated with lower risk of loneliness in adulthood. Theoretical and policy implications are discussed.